The study of learning organisations in Malaysia: Knowledge workers perspective - Daud, Md Nor Ridzuan (2004)
The use of the technology has advanced from the automation of structured processes to systems that are truly revolutionary in that they introduce change into fundamental business procedures, work flow and the management of an organisation.The study with users from different organisations with exposure to information systems was conducted to provide an in-depth insight into the trend of learning organisations in Malaysia.As a result, observation has been made that changes in organisation procedures, workflows and management require knowledge based workers.This leads to recommendations on how an organisation can develop its information systems to nurture knowledge workers